Green innovation in skincare: harnessing cucumber peel extract and gel base selection for enhanced cleansing mask efficacy - Rattanabun, Warongporn; Meenongwa , Atittaya; Pimsee, Pranudda; Warinthip, Nichthima; Jumneansree, Chonticha; Wannapokhin, Bencharat; Phoeiklin, Panit; Phungsara, Natnicha; Nakyai, Wongnapa; Keawbankrud, Wannisa (Creative Science, 2026)
This study aimed to develop a cleansing mask incorporating cucumber peel extract by systematically comparing different base gels and surfactant systems. The extraction was performed by ethanol maceration followed by rotary evaporation, yielding a 6.45 ± 0.33% extract rich in phenolic and flavonoid compounds (26.62 ± 0.51 mg GAE g⁻¹ dry extract and 14.96 ± 0.42 mg QE g⁻¹ dry extract) and exhibiting antioxidant activity (DPPH IC₅₀ = 380.67 ± 1.53 µg mL⁻¹; ABTS IC₅₀ = 384.04 ± 1.94 µg mL⁻¹). Simple gel formulas were developed with bases of Hydroxyethyl cellulose, Carbomer SF1 and Aristoflex AVC, later combined with surfactant systems (SLS/CAB or MPE) containing different proportions of cucumber peel extract. The formulations were evaluated for physical properties, sensory attributes, stability, foaming power and microstructure. Carbomer SF1 gel with SLS and CB showed the best sensorial properties and foam quality, whereas Aristoflex AVC exhibited higher viscosity (3106.08 ± 105.83 cP) and stable appearance throughout the study period. Notably, the C1 (MPBE system) generated finer microfoam and superior cleansing efficacy, underscoring the impact of base and surfactant selection on cleansing performance, antioxidant delivery and consumer acceptability, and supporting the potential of agro‑waste–derived extracts for multifunctional cosmetic masks. GRAPHICAL ABSTRACT HIGHLIGHTS Cucumber peel extract (6.45 ± 0.33%) contains rich phenolic (gallic acid equivalent: 26.62 ± 0.51mg GAE g-1) and flavonoid content (quercetin equivalent :14.96 ± 0.42mg QE g-1), performs powerful antioxidant activity. The foam quality, clarity and aesthetic appearance of cleansing masks are accomplished with a combination of 2% Sodium Lauryl Sulfate and 4% Cocamidopropyl betaine in a Carbomer SF1 gel base. The highest viscosity (3106.08 ± 105.83 cP), the best stability, and long enough duration of use can be also obtained using the Aristoflex AVC gel base (0.5%) which could support for a more long-lasting cosmetic formulations containing cucumber peel extract.